Case report: an initially unresectable stage III pulmonary sarcomatoid carcinoma qith EGFR mutation achieving pathological complete response following neoadjuvant therapy with osimertinib plus chemotherapy - Liu, Xiguang; Zheng, Yating; Mai, Shijie; Tong, Yu; Yang, Lili; Huang, Mengli; Cai, Ruijun (Frontiers in Oncology, 2022)
Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (EGFR-TKIs) provide dramatic response to patients with advanced EGFR-mutant non-small cell lung cancer (NSCLC). However, the use of neoadjuvant therapy with EGFR-TKIs in EGFR-mutant NSCLC remains controversial, especially in pulmonary sarcomatoid carcinoma (PSC). One patient with initially unresectable stage III (cT4N0M0) PSC was found to carry EGFR mutation by the next generation sequencing. After neoadjuvant therapy with osimertinib plus chemotherapy, radical resection of the right upper lung lesion was achieved, and the pathological results reached pathological complete response (pCR). To the best of our knowledge, this is the first report of an EGFR-mutant patient with initially unresectable stage III PSC achieved pCR by neoadjuvant therapy with osimertinib plus chemotherapy. Therefore, neoadjuvant therapy with EGFR-TKIs may be a viable option for EGFR-mutant PSC patients.